2018
DOI: 10.1002/slct.201801887
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Pseudo Five Component Synthesis of Biologically Relevant 1,2,6‐Triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐ carboxylates: A Decade Update

Abstract: Piperidines, an important class of N‐heterocycles, are very common in naturally occurring bioactive compounds. Recently, functionalized piperidines, specifically, 1,2,6‐triaryl‐4‐arylamino‐piperidine‐3‐ene‐3‐carboxylates have drawn considerable attention due to its diverse pharmacological efficacies that include anti‐cancer, anti‐microbial, anti‐oxidant, anti‐fungal, anti‐inflammatory and acetylcholinesterase (AChE) inhibitory activities. As a result, during the last decade, a number of methods reported for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 96 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…водных пиперидина [2,3,4,5,6,7,8,9,10,11,12,13,14], модификации [15] и их фармакологическим исследованиям [16,17,18]…”
Section: фармацияunclassified
“…водных пиперидина [2,3,4,5,6,7,8,9,10,11,12,13,14], модификации [15] и их фармакологическим исследованиям [16,17,18]…”
Section: фармацияunclassified
“…The Abbas lab reported a silica sulfuric acid (SSA)-catalyzed reaction for the syn Piperidine is a privileged N-heterocyclic ring and its derivatives possess diverse pharmacological activities such as anticancer, antimicrobial, antioxidant, antiinflammatory, and acetylcholinesterase inhibitory activities [59]. There are several papers on the synthesis of piperidine derivatives through the reaction of aromatic aldehydes, anilines, and β-keto esters under different conditions.…”
Section: Scheme 32 6c5cr For Bis(2-phenyl-23-dihydroquinazolin-4(1h)-ones)mentioning
confidence: 99%
“…Integration of bioactive heterocycles like piperidone, [15–16] pyrimidines, [17] γ ‐arylpyridine, [18–20] tetrahydropyridine… [21–23] into crown ether structures promises the enhancement of bioactivity and other interesting properties of such derivatives, especially regarding antimicrobial and antitumor properties. To our best knowledge, numerous studies about these tetrahydropyridine and piperidone derivatives were reported but mostly focused on their main function [14,24–26] . In our present studies, the efficient synthesis of crown ether compounds through the MCR of dialdehyde, β ‐keto esters and ammonium acetate are explored.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, numerous studies about these tetrahydropyridine and piperidone derivatives were reported but mostly focused on their main function. [14,[24][25][26] In our present studies, the efficient synthesis of crown ether compounds through the MCR of dialdehyde, βketo esters and ammonium acetate are explored. New derivatives of azacrownophane were successfully prepared from that with the introduction of pharmacophoric moieties namely tetrahydropyridine or piperidone cores connected with flexible polyether spacers in their molecules.…”
Section: Introductionmentioning
confidence: 99%